Effects on reproductive parameters of Nellore bulls by cottonseed addition in their diet (Research, Society and Development, 2022)
The aim of this study was to evaluate reproductive parameters of Nellore bulls by cottonseed (CS) addition with different concentrations of free gossypol in their diet. Twenty-eight animals (from 18 to 24 months) divided into 4 treatments were used in which (T1) was represented by animals that had no addition of CS (i.e. no free gossypol); (T2) addition of 860 g of CS - 1.65 g/of free gossypol/animal/day; (T3) addition of 1.72 g of CS - 3.30 g of free gossypol /animal day and (T4) addition of 2,580 g of CS - 4,95 g of free gossypol/animal/day. Blood samples for testosterone free evaluation, semen collection and testicular consistence were performed in 30-day intervals (D0, D30, D60, D90 and D120). Semen analysis consisted of of volume, appearance, pH, whirlpool, vigor, motility, concentration (/mL and /ejaculate) and sperm morphology. Testicular analysis consisted of of scrotal circumference, length and testicular width and testicular consistency. Sterilization were performed in day 121 for histopathological analysis. Free gossypol did not interfere in free testosterone, sperm concentration, major defects, scrotal circumference and testicular width. However, whirlpool, vigor, motility and minor defects were altered. Testicular length and consistence showed difference from day 60 (p